Analysis of strength on the thick plate part using genetic algorithm - Syed Mohd Azlan Syed Othman (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This study focuses on the optimisation of the injection moulding parameters to maximise the strength on the moulded part produced using Autodesk moldflow Insigth (AMI) 2012. The strength of the moulded parts moulded using acrylonitrile-butadiene styrene (ABS) has been analysed. Mould temperature, melt temperature, packing pressure and packing time were selected as aset of processing parameter.